Emotion-based approaches to personnel management emerging research and opportunities - Fazzin, Sara, 1982- (Advances in human resources management and organizational development (AHRMOD) book series., 2019)
"This book explores how an emotional approach can influence human resource practices, consumer behavior, knowledge management, managing people, and leadership skills. It also considers practical consequences to the way an organization should be managed"--